Feeding preference of pine sawyer beetle (Monochamus carolinensis) on Pinaceae and use of virtual plant walk maps as a tool for teaching plant identification courses - Wilson, Matthew Stephen (Kansas State University, 2016)
Feeding preference experiments with the pine sawyer beetle (Monochamus carolinensis Olivier) were conducted using eleven taxa of Pinaceae. One newly emerged adult beetle (≤ 24 hours) was placed into each feeding arena (n = 124) containing three or four shoots of current season's growth from different tree species (one shoot per species) for choice experiments. Beetles were allowed to feed for 48 (2011) or 72 (2012-2014) hours, at which point shoots were removed and data collected on feeding occurrence and percent feeding area. Augmented design analyses of feeding occurrence and percent feeding area of the eleven taxa did not indicate significant evidence for feeding preferences of the pine sawyer beetle on most taxa except for a higher preference for both scots (Pinus sylvestris L.) and eastern white (P. strobus L.) pines compared to deodar cedar [Cedrus deodara (Roxb. ex D. Don) G. Don]. The feeding preference experiments suggest that pine sawyer beetle may feed on a wide-range of Pinaceae taxa. Virtual plant walk maps were developed using a web-application for two semesters of an ornamental plant identification course (n = 87). The maps allowed students to revisit plants and information covered in lecture and laboratory sections at their own convenience, using either a computer or mobile device. Survey results indicated 63% of the students used the virtual plant walk maps as a study resource. Students mainly used the maps to study the most current plant list. Most students who used the virtual maps did so to review the plants online. When asked to rate usefulness of the maps on a scale from slightly useful (1) to very useful (3), 43% of students indicated that the virtual maps study tool was very useful, 25% indicated the maps were useful, and 8% indicated that the maps were slightly useful. A significant dependence between student use frequency and student usefulness ratings of virtual plant walk maps was observed. As students’ use of the virtual maps increased, they perceived the maps to be more useful to their studies in preparing for identification quizzes. No differences between plant identification quiz scores were observed between students who used and did not use the virtual plant walk maps or between learning styles. Our survey indicated students used the virtual plant walk maps as a resource and perceived the maps as a useful tool in preparation for identification quizzes.
Keywords: Cerambycidae; Bursaphelenchus xylophilus; Undergraduate education; Web-technology